The informal road to markets: Neoliberal reforms, private entrepreneurship and the informal economy in Turkey. Issue 4 (8th April 2014) - Kus, Basak
Abstract : Purpose: – The informal economy has expanded across developing countries during the last decades. Focussing on the Turkish case, the purpose of this paper is to examine the role of neoliberal reforms in this development. The author argues that neoliberal reforms produced a double-edged transformation in the regulatory environment of Turkey. On the one hand, the legal rules that constrain the operation of market forces decreased giving way to more entrepreneurial activity; while on the other hand, the state's effectiveness in "policing" the market declined. As the regulatory barriers to private entrepreneurship decreased, the regulatory barriers to informality also decreased. Private sector growth and informalization emerged as the concomitant outcomes of neoliberal reforms. Design/methodology/approach: – This paper examines how the state's changing regulatory relationship to the private sector under neoliberal reforms fostered informal economic activities through a close study of the Turkish case. Findings: – At the end of the 1980s, the Peruvian economist Hernando De Soto popularized the view that informalization resulted from government regulations imposing rigid constraints and costs on economic actors, and so would be restrained by decreasing or eliminating them. The economic developments of the past few decades challenge this view, however. The size of the informal economy has expanded in developing nations at a period when government regulations have been declining. How can we explain the increasing volume of informal economic activity in developing nations over the past few decades? And more, how can we explain that this has happened during a period when the private sector has grown, and regulatory rigidities have declined? This paper argues that the state's changing regulatory relationship to the private sector under neoliberal reforms was an important factor in the expansion of informal economic activities. Originality/value: – The implications of neoliberal reforms for economic processes have been widely studied in the social scientific literature. Only a handful of studies have explored their implications for the informal economy, however. These studies singled out factors such as the decline in public employment, weakening of labor unions, or capital's enhanced ability to exploit labor in contributing to informalization of developing country economies in the neoliberal era. By discussing how the changing regulatory contours of the state-economy relationship played a role in the growth of informally operating private enterprises, this paper adds to the existing knowledge of this relationship.